Knowledge and attitude of Basic Health Workers (BHWs) toward HIV/AIDS - Timilshina N, Ansari MA (Journal of Nepal Health Research Council, 2013)
Background: The incidence of HIV infection and AIDS is rising in Nepal. The Basic Health Workers (BHWs) are front-line services providers in rural community. The aim of this study was to ascertain BHWs concerns regarding risk awareness, knowledge and attitude toward HIV/AIDS.Methods: A stratified random sample was used to select the BHWs from two districts. Data were collected using well-structured self-administrated questionnaire. It was consists of knowledge and attitude related question. Knowledge was assessed by asking several questions concerning issues on HIV/AIDS. Attitude was measured on a five-point Likert scale. Collected data were analyzed using the Epi-Info Software.Results: A total of 100 BHWs were participated in this study. The mean age of Basic Health Workers were 39 years. Out of all the participants 69 (69%) were male and 31 (31%) were female. The present study revealed that only 46 (46%) had good knowledge and 59 (59%) differentiate between HIV and AIDS. Only 22 (22%) BHWs had accurate knowledge of Universal Precaution.Only 38 (38%) participants showed positive and rationalized feeling towards HIV/AIDS patients and 51 (51%) BHWs agreed that HIV/AIDS patients have right to live as we do. 41 (41%) were uncertain that universal precaution can prevent transmission of HIV.Conclusions: This study suggested that the Basic Health workers who participated in this study study possess basic knowledge but inadequate, although majority of them have poor attitudes toward persons with HIV/AIDS. Most incorrect answers were related to universal precaution. Ministry of Health Services, Nepal should consider the potential benefits to be gained from improving knowledge, attitude and practice of Basic Health Workers in prevention and control of rapidly increasing health problem of HIV/AIDS.